The Components of Early Intervention Services for Families Living in Poverty: A Review of the Literature. (May 2016) - Corr, Catherine; Santos, Rosa Milagros; Fowler, Susan A.
The Individuals With Disabilities Education Act mandates that very young children with disabilities be served through Part C services. Families of young children with disabilities who are also living in poverty are often the primary recipients of these services. To better understand the experiences of families, particularly those living in poverty, within the early intervention (EI) system, we reviewed four EI components: (a) family-centered orientation, (b) natural learning environments, (c) collaborative team processes, and (d) service integration. We discuss the implications of these components for the preparation and training of EI providers to work with families, including those living in poverty.